Telomere Length, Telomerase Activity, and Replicative Potential in HIV Infection: Analysis of CD4(+) and CD8(+)T Cells from HIV-discordant Monozygotic Twins - Palmer, Larry D. (The Rockefeller University Press, 1997)
To address the possible role of replicative senescence in human immunodeficiency virus (HIV) infection, telomere length, telomerase activity, and in vitro replicative capacity were assessed in peripheral blood T cells from HIV(+) and HIV(−) donors. Genetic and age-specific effects on these parameters were controlled by studying HIV-discordant pairs of monozygotic twins. Telomere terminal restriction fragment (TRF) lengths from CD4(+) T cells of HIV(+) donors were significantly greater than those from HIV(−) twins. In contrast, telomere lengths in CD8(+) T cells from HIV(+) donors were shorter than in HIV(−) donors. The in vitro replicative capacity of CD4(+) cells from HIV(+) donors was equivalent to that of HIV(−) donors in response to stimulation through T cell receptor CD3 and CD28. Little or no telomerase activity was detected in freshly isolated CD4(+) or CD8(+) lymphocytes from HIV(+) or HIV(−) donors, but was induced by in vitro stimulation of both HIV(+) and HIV(−) donor cells. These results suggest that HIV infection is associated with alterations in the population dynamics of both CD4(+) and CD8(+) T cells, but fail to provide evidence for clonal exhaustion or replicative senescence as a mechanism underlying the decline in CD4(+) T cells of HIV-infected donors.